Accuracy and Operational Characteristics of Xpert Human Immunodeficiency Virus Point-of-Care Testing at Birth and Until Week 6 in Human Immunodeficiency Virus–exposed Neonates in Tanzania. (29th June 2018) - Sabi, Issa; Mahiga, Hellen; Mgaya, Jimson; Geisenberger, Otto; Kastner, Sabine; Olomi, Willyhelmina; Saathoff, Elmar; Njovu, Lilian; Lueer, Cornelia; France, John; Maboko, Leonard; Ntinginya, Nyanda Elias; et al.
Abstract : The Xpert HIV-1 Qual demonstrated excellent performance for point-of-care human immunodeficiency virus early infant diagnosis (EID) testing using whole blood at health facilities in Tanzania. EID sensitivity at week 6 was affected, possibly due to viral suppression under nevirapine prophylaxis. Abstract: Background: Point-of-care (PoC) systems for early infant diagnosis (EID) may improve timely infant human immunodeficiency virus (HIV) management. Experiences within African public health settings are limited. Methods: We evaluated the accuracy and operational feasibility of the Xpert HIV-1 Qual for PoC-EID testing, using fresh blood and dried blood spots (DBS) samples at obstetric health facilities in Tanzania at birth and at postpartum weeks 1, 2, 3, and 6 in HIV-exposed infants. Test results were confirmed using TaqMan DBS HIV-deoxyribonucleic acid and/or plasma HIV-ribonucleic acid (RNA) testing. Results: At week 6, 15 (2.5%) out of 614 infants were diagnosed with HIV; 10 (66.7%) of them at birth (median HIV-RNA 4570 copies/mL). At birth, the Xpert-PoC and Xpert-DBS were 100% sensitive (95% confidence intervals: PoC, 69.2–100%; DBS, 66.4–100%) and 100% specific (PoC, 92.1–100%; DBS, 88.4–100%). By week 3, 5 infants with intra/postpartum HIV-infection (median HIV-RNA 1 160 000 copies/mL) were all correctly diagnosed by Xpert. In 2 cases, Xpert-PoC testing correctly identified HIV-infection when DBS tests (Xpert and TaqMan) were negative, suggesting a greater sensitivity. In 2 infants with confirmed HIV at birth, all tests were negative at week 6, possibly because of viral suppression under nevirapine prophylaxis. Problems were reported in 183/2736 (6.7%) of Xpert-PoC tests, mostly related to power cuts (57.9%). Conclusions: We demonstrated excellent Xpert HIV-1 Qual performance and good operational feasibility for PoC-EID testing at obstetric health facilities. Week 6 sensitivity issues were possibly related to nevirapine prophylaxis, supporting additional birth PoC-EID testing to avoid underdiagnosis. Clinical Trials Registration: NCT02545296